Do Not Worry About Less but Worry About Inequality: The Importance of Interactive Fairness in The Performance Appraisal of University Faculty - Wang, Chunmei; Li, Hongxia (International Journal of Multidisciplinary in Management and Tourism, 2022)
Interaction fairness is the most flexible and operable dimension in the fairness of performance assessment, involving superiors’ attitudes toward subordinates and whether information communication is comprehensive. It strongly influences faculty feelings and attitudes. It is an important variable that impacts university faculty performance appraisal satisfaction and job performance. This study explored the mediating role of appraisal satisfaction (AS) in perceived interactive fairness (PIF) and faculty job performance (JP) and the moderating effect of performance-related pay (PRP) size on the relationship between appraisal satisfaction and faculty job performance in higher education by investigating 407 teachers at a public undergraduate university in Sichuan Province of China. The results indicate that faculty members’ perceived interactive fairness and appraisal satisfaction are positively related to faculty members’ job performance. Performance appraisal satisfaction mediates the relationship between perceived appraisal interactive fairness and university faculties’ teaching performance (TP) and research performance (RP). Furthermore, appraisal satisfaction positively affects faculty members’ teaching performance when faculty members have a larger performance-related pay size. This study provided substantial support for performance appraisal characteristics and performance-related pay size research. These findings have implications for improving faculty members’ performance appraisal and performance-related pay settings. Future research is also discussed.